Diversity in Women Entrepreneurship - TEJVIR SINGH TOMAR (Dr. Chinmay Pandya, 2015)
Entrepreneurship has great scope in Indian economy. Our national economy is most suited to growth of small business enterprises which offer a more convenient means of nurturing and developing women entrepreneurship by providing the means of entry into business for new entrepreneurial talents. Women entrepreneurship is both a result of applied behavioural science as well as a normative re-educative strategy of changing. The study assumes an even greater significance in view of the current and rapid changes in the societal world. In this age of economic reforms and women empowerment more and more women are entering into a variety of employment and self-employment avenues or would be compelled into them.